Anodic electrochemical behaviors of in situ synthesized (TiB+TiC)/Ti6Al4V composites in NaNO3 and NaCl electrolyte. (1st August 2022) - Yue, Xiaokang; Qu, Ningsong; Ma, Xin; Li, Hansong
Abstract: Anodic electrochemical behaviors of the titanium matrix composites (TiB+TiC) /Ti6Al4V in 10 wt% NaNO3 and NaCl electrolytes are reported for the first time. The corrosion resistance is better in the NaNO3 electrolyte as the passive film can grow on the pitting region, which forming more stable passive film and hindering corrosion pit. Besides, the current efficiency is higher in NaNO3 electrolyte while the dissolved surface quality is significantly better in NaCl electrolyte, owing to the adhesion and mechanical loss of by-products in NaNO3 electrolyte. This research also provides guidance for better electrochemical machining in the titanium matrix composites. Graphical Abstract: ga1 Highlights: Only one porous passive film is generated on the (TiB+TiC)/Ti6Al4V in NaNO3 and NaCl electrolytes. Corrosion resistance for (TiB+TiC)/Ti6Al4V in NaNO3 electrolyte is better than that in the NaCl electrolyte. Main composition of the passive film and by-products is the same in different electrolytes. Dissolution mechanism in different electrolytes is illustrated to explain the dissolved distinctions.